Relações intersemióticas em reportagens de capa de Superinteressante - Ferreira, Janaina Carvalho (2012)
The main goal of the present study is to investigate the intersemiotic relations between text and image in feature articles from the Brazilian popular science magazine Superinteressante. The corpus consists of 12 multimodal feature articles published between February and December, 2009. This particular time period was chosen because in August of the same year the magazine implemented a visual remodeling, and in order to examine to what extent this affected the roles of text and image in the genre, we chose the six issues published immediately before the change (from February to July, 2009 - Phase 1) and the six issues published immediately after the change (from August to December, 2009 - Phase 2). In addition to intersemiotic relations, we also compared the issues in terms of visual transformations based on the Grammar of Visual Design (KRESS; VAN LEEUWEN, 1996; 2006). The analysis of the intersemiotic relations was guided by the system of status and logico-semantic image-text relations proposed by Martinec and Salway (2005). The results show that the visual remodeling affected the genre, as the role of images was extended from an essentially interpersonal function in Phase 1 to greater representational value in Phase 2, as drawings, schemes, graphs and maps carry content which is not in the verbal language of the feature articles. The analysis of the intersemiotic relations of two exemplars revealed that, in Phase 1, the status between text and image is predominantly unequal, with the image being subordinated to the text, while in Phase 2 the status between both languages is equal. Considering logico-semantic relations, in Phase 1, most of the times the text adds information to the image, in a logico-semantic relation of Expansion, while in Phase 2, the information in text and image have the same level of generality, in a logico-semantic relation of Exposition. These findings contribute to support the argument about the increasing importance of visual language in contemporary communication, which in turn highlight the need for the development of multiliteracies.